2009
DOI: 10.1175/2009jcli2465.1
|View full text |Cite
|
Sign up to set email alerts
|

The Great 2006 Heat Wave over California and Nevada: Signal of an Increasing Trend

Abstract: Most of the great California–Nevada heat waves can be classified into primarily daytime or nighttime events depending on whether atmospheric conditions are dry or humid. A rash of nighttime-accentuated events in the last decade was punctuated by an unusually intense case in July 2006, which was the largest heat wave on record (1948–2006). Generally, there is a positive trend in heat wave activity over the entire region that is expressed most strongly and clearly in nighttime rather than daytime temperature ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
159
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(169 citation statements)
references
References 32 publications
9
159
0
1
Order By: Relevance
“…In addition, the results reproduced in the present paper are analogous to those found in other Mediterranean Regions, using the RAMS model (Pasqui et al, 2004;Federico, 2011), and using other real-time mesoscale models (Bartzokas et al, 2010). Likewise, considering other areas with Mediterranean-type climate regimes, it has been found that atmospheric humidity is the main cause of elevated minimum temperatures in the summer (Gershunov et al, 2009). In contrast, taking into account the temperature field within this season of the year, a cold bias was identified in RAMS simulations over east-central Florida (Case et al, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the results reproduced in the present paper are analogous to those found in other Mediterranean Regions, using the RAMS model (Pasqui et al, 2004;Federico, 2011), and using other real-time mesoscale models (Bartzokas et al, 2010). Likewise, considering other areas with Mediterranean-type climate regimes, it has been found that atmospheric humidity is the main cause of elevated minimum temperatures in the summer (Gershunov et al, 2009). In contrast, taking into account the temperature field within this season of the year, a cold bias was identified in RAMS simulations over east-central Florida (Case et al, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…Unlike in AF1, in the AF2 and Natural experiments, daily maximum and minimum temperature were archived for each day of the year, which permited the calculation of Tmin_hi; this is advantageous for the analysis given its increased role in recent heat extremes (Gershunov et al 2009). AF1 has 5-day intervals of specific humidity, allowing for analysis of WBGT in the supplementary materials.…”
Section: Model Analysismentioning
confidence: 99%
“…1). This domain is chosen because of its general spatial coherence in terms of its summer climatology at lower elevations and because it has been analyzed extensively in the literature (Gershunov et al 2009;Walsh et al 2014). Decadal anomalies are calculated as the differences from the mean over the period 1901-1960. The CA/NV domain's JJA Tmax_hi (Fig.…”
Section: Decadal Temperature Anomalies In the Observationsmentioning
confidence: 99%
See 2 more Smart Citations